MENINGKATKAN KOMPETENSI PEDAGOGIK UNTUK MENYUSUN RPP MELALUI BIMBINGAN SUPERVISI DI SMP NEGERI 2 MUKO-MUKO BATHIN VII - Ramaili, Ramaili (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2021)
The ability to plan lessons is an academic competency that teachers need to develop professionally. This study aims to improve the pedagogical competence of teachers at SMP Negeri 2 Muko-Muko Bathin VII in preparing lesson plans through supervision activities. This study used a School Action Research (PTS) design. This study was carried out in two cycles including PTS principles, namely planning, implementing, observing, and reflecting in each cycle. with descriptive qualitative data processing. The research subjects were teachers of SMP Negeri 2 Muko-Muko Bathin VII. Data collection techniques through observation, interviews, and document analysis. The results showed an increase in the ability of teachers to prepare lesson plans through supervisory guidance. The increase in ability can be seen from the results of the evaluation by applying supervisory guidance to teachers in cycle I and cycle II. The teacher shows seriousness and understands the preparation of RPP Curriculum 2013 after receiving guidance for the preparation of RPP. The results of the actions of each cycle show the results of cycle 1 with an average value of 63.75, and cycle 2 with an average value of 77.50. There is an increase in the total value from 50% to 100%. Thus it can be emphasized that supervision guidance can be used as an alternative to improve the pedagogical ability of SMP Negeri 2 Muko-Muko teachers in preparing lesson plans.